Neonatal Onset of Epilepsy of Infancy with Migrating Focal Seizures Associated with a Novel GABRB3 Variant in Monozygotic Twins - Štěrbová, Katalin; Vlčková, Markéta; Klement, Petr; Neupauerová, Jana; Staněk, David; Zůnová, Hana; Seeman, Pavel; Laššuthová, Petra (Neuropediatrics, 2018)
BACKGROUND: Recently, a study providing insight into GABRB3 mutational spectrum was published (Møller et al 2017). The authors report considerable pleiotropy even for single mutations and were not able to identify any genotype-phenotype correlations. METHODS: The proband (twin B) was referred for massively parallel sequencing of epilepsy-related gene panel because of hypotonia and neonatal seizures. The revealed variant was confirmed with Sanger sequencing in the proband and the twin A, and both parents were tested for the presence of the variant. RESULTS: We report a case of epilepsy of infancy with migrating focal seizures (EIMFS) of neonatal onset in monozygotic twins with a de novo novel GABRB3 variant p.Thr281Ala. The variant has a uniform presentation on an identical genomic background. In addition, early seizure-onset epilepsy associated with GABRB3 mutation has been until now described only for the p.Leu256Gln variant in the GABRB3 (Møller et al 2017, Myers et al 2016) located in the transmembrane domain just as the p.Thr281Ala variant described here. CONCLUSION: De novo GABRB3 mutations may cause neonatal-onset EIMFS with early-onset hypotonia, respiratory distress, and severe developmental delay.
Keywords: nemoci u dvojčat; Epilepsy; Receptors, GABA-A; epilepsie; kojenec; věk při počátku nemoci; dvojčata monozygotní; mutace; Infant; Twins, Monozygotic; Infant, Newborn; Diseases in Twins; ženské pohlaví; novorozenec; Mutation; Humans; Age of Onset; receptory GABA-A; Female; lidé